2021
DOI: 10.33448/rsd-v10i14.21818
|View full text |Cite
|
Sign up to set email alerts
|

Use of superabsorbent polymers in cement-based compounds: a bibliometric analysis

Abstract: Superabsorbent polymers (SAP) have gained the attention of the engineering field for applications in cementitious composites. Recently, many studies have addressed using these materials as an alternative to controlling recurrent pathologies, especially retraction in the hardening stage. This study conducted a literature review in the Scopus and Web of Science databases to identify relevant studies for future research in this area. Analyses were performed using the RStudio software program, where data on the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The use of SAP with self-compacting cement and mortar is underexplored; some studies have proven that it has advantages in the utilization of conventional cement composites, being of significant help to counter retractions in the curing process [13]. In [14], SAP in two diameters (600 µm and 800 µm) was added to self-compacting cement pastes, where increases in compressive strength of 35.2% and 34.3%, respectively, were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…The use of SAP with self-compacting cement and mortar is underexplored; some studies have proven that it has advantages in the utilization of conventional cement composites, being of significant help to counter retractions in the curing process [13]. In [14], SAP in two diameters (600 µm and 800 µm) was added to self-compacting cement pastes, where increases in compressive strength of 35.2% and 34.3%, respectively, were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…The Figure 1 shows the research field related to the theme sludge, water treatment plant, concrete and mortar, trend of the research field, theme sludge with cementitious composites. This search was conducted in the Scopus database and reveals the small number of studies on the subject, despite an increase in the last decade, with the year 2020 being the one with the highest number of publications (Souza et al, 2021). In light of the above, this study aims to analyze the replacement of cement in 10 and 20% by WTS in the production of mortar, in order to reduce the impact of the extraction of materials for construction and give an appropriate destination for the sludge generated in the water treatment plant of Itajubá Minas Gerais.…”
Section: Introductionmentioning
confidence: 99%
“…According to Souza et al [ 1 ] the number of articles published in the area of concrete/mortar/paste and superabsorbent polymer throughout history showed an increase in the number of publications in the two databases analyzed (Scopus and Web of Science (WOS)). The authors showed a promising scenario for publications related to this subject, especially because the last 5 years accounted for more than 70% of all publications throughout history.…”
Section: Introductionmentioning
confidence: 99%